Evaluation Of K3 Management And Risk Analysis In The Factory Environment - Herotje Siwi; Jedithjah Naapia Tamedi Papia; Meike Negawati Kesek (International Journal of Artificial Intelligence Research, 2026)
This study aims to evaluate the implementation of K3 management and analyze the level of occupational risk in a manufacturing plant. The implementation of an K3 management system is a crucial aspect in maintaining worker safety, increasing productivity, and minimizing the potential for workplace accidents that could harm both the company and workers. The study used a descriptive quantitative approach, employing field observations, interviews, documentation, and questionnaires distributed to 150 respondents, including production operators, technical staff, and factory supervisors. Risk analysis was conducted using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method to identify potential hazards and determine the level of risk for each work activity.The results indicate that the implementation of K3 management in the factory environment has been quite successful. However, several weaknesses remain in the supervision of personal protective equipment (PPE) use, compliance with work procedures, and risk control of production machinery. Based on the hazard identification results, several dominant risks with high levels of risk were identified, namely noise exposure, accidents caused by production machinery, potential fires, and fatigue due to excessive workload. The evaluation revealed that the lack of regular training and low worker awareness were the main factors affecting the effectiveness of K3 implementation.This study also found that the implementation of administrative and technical risk controls can significantly reduce the potential for workplace accidents if implemented consistently. Furthermore, company management involvement in routine monitoring and evaluation is a crucial factor in improving occupational safety culture in industrial environments. This study recommends improving K3 training programs, strengthening monitoring systems, and optimizing the implementation of standard operating procedures (SOPs) to minimize occupational risks in the factory environment. With effective implementation of K3 management, companies can create a safe, healthy, and productive work environment for all workers.